Goddard Suggests Ways To Help the Panmen - Goddard, George (Express)
George Goddard comments that while the Government of Trinidad and Tobago will be sponsoring a Steelband Conference, it is doubtful that any good would emerge since over the years government has failed to implement the recommendations submitted by the Association of Steelbandsmen. Goddard states that the main problem faced by the panmen is that of finance and suggests ways to help the panmen.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Musicians -- Employment -- Trinidad and Tobago; Steel bands (Music) -- Finance